Audit of Atypical Femoral Fractures and a Description of Some of Their Features. Issue 1 (February 2016) - Lian, Kevin; Trollip, Jacques; Sandhu, Supna; Moosavi, Mandana; Gill, Amninder; Kendler, David; Dian, Larry; Lentle, Brian
Purpose: Atypical femoral fractures (AFF) are recently described events related to osteoporosis and, potentially, a rare result of antiresorptive treatment. Methods: We set out to audit the diagnosis of AFF in an acute hospital. Charts and radiographs were reviewed retrospectively from patients diagnosed with subtrochanteric femoral fractures according to hospital discharge coding at Vancouver General Hospital (VGH), Canada, from January 2005 to March 2013. Results: A total of 3084 patients were discharged from the hospital with a diagnosis of hip fracture between 2005 and 2013. Of these, 204 were coded as having had subtrochanteric fractures; 178 of the patients thus coded had radiographic evidence of other fracture types—usually intertrochanteric fractures. Eleven patients did not have available radiographs. Of the remaining 193 patients whose radiographs were reviewed, 24 (12.4%) fulfilled the published criteria for AFF. Our observations were: 1) laterality: 13 of 24 AFF (54.2%) were right-sided; 2) there was only one incomplete AFF in this series: a completed fracture was an inclusion criterion, but 1 patient with an AFF had both that fracture and an incomplete fracture and further foci of periosteal or endosteal foci of new bone (PENB) involving the contralateral femur; 3) radiologists had only diagnosed AFF in only 1 of the 24 patients with characteristic radiographic signs of AFF; 4) all but 1 patient had a focus of periosteal and/or endosteal new bone (PENB) through which the fracture line invariably passed, and in the 1 exception the radiography was too poor to be sure of this but there was a symmetrical contralateral focus of PENB; 5) in 19 of 24 patients there was an adequate image of part of the contralateral femur and of these 12 (63%) had a contralateral focus of PENB situated ±2.5 cm from the index lesion site when measured from the upper aspect of the greater trochanter, and in another patient a prior fracture of the contralateral femur had been treated surgically and it was at a symmetrical contralateral location from the index fracture.; 6) in 3 of the 19 patients multiple foci of PENB were detected on the lateral aspect of the contralateral femur even though the examination was of limited extent; and 7) AFFs were associated with bisphosphonate medication in 75% of the patients studied. Conclusions: Hospital discharge coding misclassified a great majority of femoral fractures as subtrochanteric. As an essential criteria for diagnosing AFF is their subtrochanteric location, this misclassification impaired our ability to retrospectively search for AFF patients. Radiologists tended not to report AFF when typical radiographic characteristics were present. Bilateral and multifocal disease is of interest in pointing to the diagnosis and in suggesting that the mechanism of injury in respect of these unusual fractures is more complex than simple low-energy trauma.